IMPACT OF AIRBORNE FUNGAL SPORES ON HUMAN AND CROP HEALTH IN INDIA - Kumari, Sanju; Kumar, Amar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Allergic conditions, including bronchial asthma, allergic rhinitis, and atopic dermatitis, affect more than 20-30% of the world's population. These disorders are frequently caused by bioparticulates, such as fungus spores, dust mites, insect debris, and pieces from plants and foods. In order to effectively manage these allergies, it is crucial to have a comprehensive awareness of the daily, seasonal, and yearly fluctuations in the levels of these biological particles in the atmosphere. This paper examines aerobiological studies carried out in several parts of India, with a specific focus on the occurrence and seasonal patterns of fungal spores, which play a crucial role in causing allergic reactions. Thorough experiments have been conducted to ascertain the concentration of fungal spores in various habitats and monitor their seasonal variations. The key findings suggest that fungal spores are present in both indoor and outdoor contexts. Notable examples include Aspergilli-Penicilli, Cladosporium, Ascospores, Alternaria, Dreschlera, Epicoccum, Nigrospora, and Basidiospores. Some clinically significant fungal allergens that have been identified include species such as Aspergillus fumigatus, Aspergillus flavus, Aspergillus nidulans, Alternaria alternata, Cladosporium cladosporoides, Ganoderma lucidum, Mucor mucedo, Fusarium solanii, Curvularia lunata, Neurospora sitophila, and Scopulariopsis brevicaulis. The review emphasizes the importance of monitoring the atmospheric concentrations of these allergens in order to enhance diagnostic and treatment strategies for allergic disorders. Gaining insight into the dispersion and diversity of allergies is essential for formulating specific approaches to managing them and improving the well-being of persons impacted by allergic reactions.